7x-2(x-1)=6(1-x)+18

Simple and best practice solution for 7x-2(x-1)=6(1-x)+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-2(x-1)=6(1-x)+18 equation:


Simplifying
7x + -2(x + -1) = 6(1 + -1x) + 18

Reorder the terms:
7x + -2(-1 + x) = 6(1 + -1x) + 18
7x + (-1 * -2 + x * -2) = 6(1 + -1x) + 18
7x + (2 + -2x) = 6(1 + -1x) + 18

Reorder the terms:
2 + 7x + -2x = 6(1 + -1x) + 18

Combine like terms: 7x + -2x = 5x
2 + 5x = 6(1 + -1x) + 18
2 + 5x = (1 * 6 + -1x * 6) + 18
2 + 5x = (6 + -6x) + 18

Reorder the terms:
2 + 5x = 6 + 18 + -6x

Combine like terms: 6 + 18 = 24
2 + 5x = 24 + -6x

Solving
2 + 5x = 24 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
2 + 5x + 6x = 24 + -6x + 6x

Combine like terms: 5x + 6x = 11x
2 + 11x = 24 + -6x + 6x

Combine like terms: -6x + 6x = 0
2 + 11x = 24 + 0
2 + 11x = 24

Add '-2' to each side of the equation.
2 + -2 + 11x = 24 + -2

Combine like terms: 2 + -2 = 0
0 + 11x = 24 + -2
11x = 24 + -2

Combine like terms: 24 + -2 = 22
11x = 22

Divide each side by '11'.
x = 2

Simplifying
x = 2

See similar equations:

| 9x^4-3x^2+12x= | | (x+24)+(x+10)=180 | | 7u+21= | | 3/4x1/3x2/1 | | 5f-11=34 | | 10-9b=-7b-10 | | 40=-3v | | 7-6x/9x=15 | | 1/7x80 | | 9+7q=-5-10-5q | | 16x+19=180 | | 2a-86-3a=10 | | (6rs^2)(s^3t^2)(1/2r^4t^3) | | 7X-7=-7X+49 | | a+5b+10c+25d=48 | | 4+8j=6j+10 | | 2p=10-3p | | 10+4v=-v | | x+(4x-20)=180 | | v=-v-6 | | X-1)1/4=-6 | | 8+6t=8+3t | | 3d-7=10d | | 3x-2=5+3x | | 6f-4=8f | | 1=1-3x-7x | | 8-8f=-1-9f | | x^2+20x-4900=0 | | (x+2)+(3x+6)=180 | | 2x+5+6=17 | | (X^2+6)(x^2+5)=0 | | f(x)=2x^4-5x^2+2x |

Equations solver categories